The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/adfm.202206995
|View full text |Cite
|
Sign up to set email alerts
|

Nanopatterning on Mixed Halide Perovskites for Promoting Photocurrent Generation of Flexible Photodetector

Abstract: Nanoimprinting lithography (NIL) technique is widely utilized for nanostructure engineering of soft materials. Owing to the soft organic/inorganic hybrid nature, the optical and crystallographic properties of halide perovskites (HPs) are improved by the NIL process. However, the wide application of NIL into various HPs has lagged. Herein, a defect‐free nanopatterned‐(FAPbI3)0.85(MAPbBr3)0.15 (NP‐FAMA) film is successfully developed via optimized NIL. As surface energy is a key parameter to be controlled for ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Chun et al employed NIL on mixed HPs to enhance the photocurrent generation of flexible photodetectors. [82] Their study demonstrated that nanopatterning allows precise control over device structures and morphologies, leading to higher photoconversion efficiency. An et al utilized nanoimprinting to fabricate highly aligned CsCu 2 I 3 nanowires to develop highly responsive, polarization-sensitive, flexible, and stable photodetectors.…”
Section: Nanoimprint Lithography For Crystalline Materialsmentioning
confidence: 99%
“…Chun et al employed NIL on mixed HPs to enhance the photocurrent generation of flexible photodetectors. [82] Their study demonstrated that nanopatterning allows precise control over device structures and morphologies, leading to higher photoconversion efficiency. An et al utilized nanoimprinting to fabricate highly aligned CsCu 2 I 3 nanowires to develop highly responsive, polarization-sensitive, flexible, and stable photodetectors.…”
Section: Nanoimprint Lithography For Crystalline Materialsmentioning
confidence: 99%